2010
DOI: 10.3758/lb.38.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Testing the translational-symmetry hypothesis of abstract-concept learning in pigeons

Abstract: The translational-symmetry hypothesis of abstract-concept learning was tested in a same/different (S/D) task with pairs of pictures. The translational-symmetry hypothesis proposes that subjects discriminate same trials by the simultaneous repetition of features in the two pictures (and different trials by the lack of feature repetition). Pigeons that had learned a simultaneous S/D task were tested with delays between the two pictures to remove emergent perceptual cues. In Experiment 1, we tested delays of 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This proposal is supported by recent research revealing simultaneous control by both absolute and relational properties of the stimuli in same-different discriminations and in categorization tasks (Bodily et al, 2008;Gibson & Wasserman, 2003;Katz, Wright, & Bachevalier, 2002;Lazareva, Freiburger, & Wasserman, 2004). Our model also fits with empirical and theoretical work suggesting that relational choices in the same-different task cannot be explained solely by generalization from the training exemplars to the novel testing stimuli (Katz, Sturz, & Wright, 2010;Wright & Katz, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…This proposal is supported by recent research revealing simultaneous control by both absolute and relational properties of the stimuli in same-different discriminations and in categorization tasks (Bodily et al, 2008;Gibson & Wasserman, 2003;Katz, Wright, & Bachevalier, 2002;Lazareva, Freiburger, & Wasserman, 2004). Our model also fits with empirical and theoretical work suggesting that relational choices in the same-different task cannot be explained solely by generalization from the training exemplars to the novel testing stimuli (Katz, Sturz, & Wright, 2010;Wright & Katz, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Second, our modeling of faster learning with increasing set size ruled out stimulus generalization as a contributor to abstract-concept learning (Wright & Katz, 2007). Third, our subjects’ rapid transition to delays (1–2 s) ruled out possible effects of low-level translational-symmetry cues on same trials, trials with two identical pictures, and entropy cues on different trials, trials with two different pictures (Katz, Sturz, & Wright, 2010; Wright et al, 2003). Fourth, our proactive-interference tests using the delayed (1 s, 10 s, or 20 s) same/different task verified that our subjects were making bona fide relational stimulus comparisons across as many as eight trials and 5 min before testing (Devkar & Wright, 2016; Wright, Katz, & Ma, 2012).…”
mentioning
confidence: 97%
“…Counter to this prediction, performance on same and different trials showed a similar pattern across delay. Translational-symmetry has also been experimentally rejected as an explanation for the nonhuman primate results in similar procedures (Katz et al, 2010;Wright et al, 2003). In the absence of evidence to the contrary, we suggest that the species tested here, Blackbilled magpies (Pica hudsonia), learn the same/different procedure using a similar strategy to the pigeons previously tested.…”
Section: Discussionmentioning
confidence: 50%
“…Although not directly addressed by the current data, we have previously explored this theory in detail using subjects trained in the identical procedure. Katz, Sturz, and Wright (2010) trained pigeons using the current same/different procedure and, once the subjects showed full concept learning, they were transferred to a delayed same/ different task. In this task, the sample stimulus is removed following the observing response, and then comparison stimulus and white box (different choice) are presented after a variable delay (from 0 s to 6 s).…”
Section: Discussionmentioning
confidence: 99%